Analisis Kebutuhan Pengembangan Elektronik Bahan Ajar Berbasis Model LOK-R (Literasi, Orientasi, Kolaborasi dan Refleksi) untuk Siswa Sekolah Dasar - Lorenza, Sovia; Badeni, Badeni; Winarni, Endang Widi (Universitas Sebelas Maret, 2025)
Integrating technology is very important to carry out learning in this era. In addition, literacy improvement continues to be encouraged to improve students' literacy skills, including through social studies learning in the classroom. This study aims to describe the presentation of social studies books for class V which is reviewed from the aspects of the literacy model, orientation, collaboration and reflection stages. In addition, it also reviews aspects of integrating technology through the learning process presented in the book. This study uses a qualitative descriptive method with key instruments, namely the researcher with an analysis guideline. The research was carried out with an analysis sheet through a qualitative descriptive approach with data analysis techniques in the form of content analysis. Data collection was carried out using document analysis with stages of data reduction, presentation and conclusion drawn. The results of the study show that there is no integration of technology presented in the IPAS book of social studies materials, and the lack of specific stages of the LOK-R (Literacy, Orientation, Collaboration and Reflection) model that can help students develop their literacy, so it can be concluded that it is very important to carry out the electronic development of teaching materials based on the LOK-R model for elementary school students.Pengintegrasian teknologi begitu penting untuk menyelenggarakan pembelajaran di era ini. Selain itu, peningkatan literasi terus digalakkan untuk meningkatkan kemampuan siswa dalam berliterasi termasuk melalui pembelajaran IPS di kelas. Penelitian ini bertujuan untuk mendeskripsikan sajian buku IPAS materi IPS kelas V yang ditinjau dari aspek tahapan model literasi, orientasi, kolaborasi dan refleksi. Selain itu juga meninjau terkait aspek pengintegrasian teknologi melalui proses pembelajaran yang disajikan dalam buku. Penelitian ini menggunakan metode deskriptif kualitatif dengan instrumen kunci yaitu peneliti dengan lembar pedoman analisis. Penelitian dilakukan dengan lembar analisis melalui pendekatan deskriptif kualitatif dengan teknik analisis data berupa analisis isi. Pengumpulan data dilakukan menggunakan analisis dokumen dengan tahapan reduksi data, penyajian dan penarikan kesimpulan. Hasil penelitian menunjukkan tidak adanya pengintegrasian teknologi yang disajikan dalam buku IPAS materi IPS, dan minimnya tahapan model LOK-R (Literasi, Orientasi, Kolaborasi dan Refleksi) secara spesifik yang dapat membantu siswa mengembangkan literasinya, sehingga dapat disimpulkan sangat penting untuk dilakukan pengembangan elektronik bahan ajar berbasis model LOK-R untuk siswa sekolah dasar.